2013
DOI: 10.1016/j.bpj.2013.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Optoporation and Genetic Manipulation of Cells Using Femtosecond Laser Pulses

Abstract: Femtosecond laser optoporation is a powerful technique to introduce membrane-impermeable molecules, such as DNA plasmids, into targeted cells in culture, yet only a narrow range of laser regimes have been explored. In addition, the dynamics of the laser-produced membrane pores and the effect of pore behavior on cell viability and transfection efficiency remain poorly elucidated. We studied optoporation in cultured cells using tightly focused femtosecond laser pulses in two irradiation regimes: millions of low-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
69
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 31 publications
1
69
0
Order By: Relevance
“…Interestingly, it was shown that large membrane laser-induced holes are, counter-intuitively, associated with a faster resealing dynamics compared to small holes, suggesting an active resealing mechanism triggered by large membrane damages. 28 Our results can be compared to recent measurements on cell optoporation by pairs of 100 fs BWL pulses at 1 kHz from an amplified Ti:Sapphire laser. 28 The authors report successful poration and transfection with cell viability figures comparable to those obtained in pJ-level oscillator-based experiments.…”
Section: Figmentioning
confidence: 62%
See 1 more Smart Citation
“…Interestingly, it was shown that large membrane laser-induced holes are, counter-intuitively, associated with a faster resealing dynamics compared to small holes, suggesting an active resealing mechanism triggered by large membrane damages. 28 Our results can be compared to recent measurements on cell optoporation by pairs of 100 fs BWL pulses at 1 kHz from an amplified Ti:Sapphire laser. 28 The authors report successful poration and transfection with cell viability figures comparable to those obtained in pJ-level oscillator-based experiments.…”
Section: Figmentioning
confidence: 62%
“…28 Our results can be compared to recent measurements on cell optoporation by pairs of 100 fs BWL pulses at 1 kHz from an amplified Ti:Sapphire laser. 28 The authors report successful poration and transfection with cell viability figures comparable to those obtained in pJ-level oscillator-based experiments. 14 As those measurements were performed by BWL pulses, we could expect by spectral pulse shaping similar-or better-transfection rate and increased viability thanks to the 25% reduction in energy and 88% reduction in peak intensity associated with TAP+.…”
Section: Figmentioning
confidence: 62%
“…Both dyes have previously been used in literature to investigate flow in-and outside of cells [37,38]. We labeled C2C12 cells with 1 µM Calcein AM in PBS for 10 min at 37° C and washed once to reduce background fluorescence.…”
Section: Cell Culture Labeling With Dyesmentioning
confidence: 99%
“…The use of laser-based methods for cell transfection is an active area of research, because they can selectively target individual cells within a mixed cell population and specific cells of interest within a cell cluster (or possibly even in living tissue). Various methods for opto-poration of the cell membrane have been developed in recent years (Tirlapur & König 2002;Vogel et al 2005;Baumgart et al 2008;Antkowiak et al 2010;Stevenson et al 2010;Antkowiak et al 2013a,b;Davis et al 2013). Usually, a laser pulse is focused onto the cell membrane in order to create a hole.…”
Section: Implications For Opto-injectionmentioning
confidence: 99%
“…This implies the possibility of achieving a combination of a massive and slow jet opposed by a thin and fast jet that could be useful for various applications, for instance micropumping and opto-injection for cell transfection Stevenson et al 2010). The use of laser-based methods for introducing genetic materials or other substances into living cells has become a very active area of research, and various techniques for opto-poration of the cell membrane have been developed (Tirlapur & König 2002;Vogel et al 2005;Baumgart et al 2008;Stevenson et al 2010;Antkowiak et al 2013a,b;Davis et al 2013). They usually rely on creating one or several small holes in the cell membrane, and share the drawback that material transport into the cell relies on diffusion, which is a slow process.…”
mentioning
confidence: 99%